2018
DOI: 10.4238/gmr18161
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genetic diversity of three indigenous pig breeds in Colombia

Abstract: Zungo (ZU), San Pedreño (SP) and Casco de Mula (CM) are Colombian indigenous pig breeds originated from European populations that are well adapted to tropical conditions. These breeds have a great potential to be used in pure and crossbred schemes due to their high reproductive performance and resistance to tropical diseases. We investigated the genetic diversity and genetic structure of these pig breeds using microsatellite molecular markers. Fifty-five ZU, SP and CM animals were genotyped for 10 microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
0
1
3
Order By: Relevance
“…The high θ estimate in our study is in agreement with the results reported by Gama et al [ 12 ] for native pig breeds from Iberia and its islands (20%) and other studies with European pig breeds, where θ has ranged from 21% [ 70 ] to 27% [ 71 ]. However, our estimate is higher than some results reported for Criollo pig populations alone (11%) [ 11 ] or for Colombian pig breeds (10%) [ 72 ]. The degree of breed differentiation found here is also substantially higher than the between-breed diversity component reported in studies with other livestock species where Criollo breeds were also included, such as cattle [ 5 ], donkeys [ 59 ], horses [ 57 ] and goats [ 58 ].…”
Section: Discussioncontrasting
confidence: 88%
“…The high θ estimate in our study is in agreement with the results reported by Gama et al [ 12 ] for native pig breeds from Iberia and its islands (20%) and other studies with European pig breeds, where θ has ranged from 21% [ 70 ] to 27% [ 71 ]. However, our estimate is higher than some results reported for Criollo pig populations alone (11%) [ 11 ] or for Colombian pig breeds (10%) [ 72 ]. The degree of breed differentiation found here is also substantially higher than the between-breed diversity component reported in studies with other livestock species where Criollo breeds were also included, such as cattle [ 5 ], donkeys [ 59 ], horses [ 57 ] and goats [ 58 ].…”
Section: Discussioncontrasting
confidence: 88%
“…Al comparar los resultados obtenidos para cada marcador en cuanto a "F ST ", se nota que los microsatélites S0225, SW24, SW632, SW911 y SW936 son moderadamente sensibles para detectar la diferenciación en las poblaciones analizadas con la metodología utilizada, debido a que su valor es inferior al 0.1. Este resultado converge con los reportes de Martínez et al (2004) y Rocha et al (2018). El Valor de "F ST " multilocus refleja la proporción de variación genética debida a la diferenciación entre razas o variedades dentro de la población (Martínez et al, 2000; Yang et al, 2003, el cual para el presente estudio se ubicó en 0.125, siendo su equivalente (Nei, 1973) el "G ST " que resultó en 0.136 (Cuadro 1).…”
Section: Resultados Y Discusiónunclassified
“…La subdivisión entre grupos de cerdos criollos y autóctonos fue reportada con anterioridad por Lemus et al (2001), Yang et al (2003), Vicente et al (2008) y Rocha et al (2018) coincidiendo en su mayoría, al igual que en el presente trabajo, con los orígenes geográficos de los mismos. Asimismo, la separación entre los Ibéricos -Alentejanos y razas comerciales, ha sido reportada en la literatura (Martínez et al, 2000; Fabuel et al, 2004; Pérez et al, 2005; Vicente et al, 2008.…”
Section: Resultados Y Discusiónunclassified
“…El potencial de un MG para su uso en pruebas genéticas depende del HW y DL, así como la variabilidad genética expresada; en poblaciones de CPM se han realizados estudios de caracterización genética con base en MG de tipo microsatélite (Lemus-Flores et al, 2001;Canul et al, 2005). En otras poblaciones de cerdos criollos también han evaluado la variabilidad genética con fines de conservación y mejora genética utilizando MG de tipo microsatélites (Jimenez et al, 2017;Margeta et al, 2018;Rocha et al, 2018); todos los trabajos afines coinciden en la necesidad de implementar programas de conservación con el objetivo de proteger la variabilidad genética. En las pruebas de paternidad las probabilidades de exclusión y no exclusión están en función de las frecuencias alélicas en los progenitores y sus probabilidades de trasmisión a la progenie.…”
Section: Discussionunclassified